Nutritional and physico-chemical properties of egg powder are aﬀected by diﬀerent drying methods - Akyereko, Yaw Gyau; Opoku Edusei, Vida; Adu, Maxwell; Odoi Anim, Solomon; Benewaa Yeboah, Georgina; Dufie Wireko-Manu, Faustina (Food Agricultural Sciences and Technology, 2025)
This research aimed to determine the effect of solar and freeze-drying methods on the nutritional and physico-chemical properties of egg powder. Fresh egg samples were dried separately using solar and freeze-drying, and the physico-chemical properties, proximate, and mineral content were determined using standard methods. For the physico-chemical properties, solar drying caused a reduction in the TSS and pH from 0.83 °Brix and 7.95 for fresh egg to 0.55 °Brix and 6.89 (solar-dried egg powder) compared to that (0.95 °Brix and 7.73) of freeze-drying, though both methods had no effect on TTA. The drying methods reduced the color characteristics (L*-41.62, a*-2.68, and b*-15.88) of the fresh egg to (L*-34.27, a*-0.51, and b*-13.29) and (L*-28.08, a*-0.91, and b*-5.74) for freeze- and solar-dried egg powders, respectively. Except for moisture (75.98%), which decreased significantly to 2.32% (freeze-drying) and 6.70% (solar drying), protein (54.40-55.93%), fat (27.75-29.49%), ash (4.14-4.58%), carbohydrate (7.03-7.69%), and energy (485.41-519.83%) increased greatly for the egg powders compared to the fresh egg, which had 10.62%, 8.32%, 1.54%, 2.21%, and 130.56 kcal correspondingly. The two egg powders had comparable concentrations of K, Ca, Fe, Zn, and Mg, indicating equal effects of freeze- and solar-drying methods on mineral composition. The freeze-drying was more efficient in moisture removal and maintaining a high nutritional profile as well as color characteristics of the egg powder, and therefore presents a high potential for commercial production of egg powder to promote food and nutrition security.